Exploring Undergraduate Students’ Understanding of the Limit of a Function - Chand, Harsh Bahadur; Luitel, Bal Chandra; Pant, Binod Prasad; Belbase, Shashidhar (Academic Journal of Mathematics Education, 2024)
The concept of limit of a function is a foundational in undergraduate Calculus and Real Analysis. While previous studies have identified various misconceptions and difficulties students face regarding this concept, there appears to be a lack of studies examining undergraduate students’ understanding of the concept of limit in Nepali universities. In this regard, this study was carried out to explore undergraduate students’ understanding of the concept of a limit of a function. Adopting a qualitative research design with interpretive paradigm, we conducted semi-structured interviews with six students studying Bachelor of Education (B.Ed.) in the fifth semester at one of the universities in Nepal. Four major themes emerged from the interview data through an iterative process of coding and thematizing. These themes were: (i) limited ability to construct and connect multiple representations, (ii) weak interconnections among the concepts, (iii) highly deviated subjective knowledge resulted lack of meaningful learning, and (iv) lack of conceptual understanding due to inadequate vocabulary and logical proficiency. The insights from this study have significant implications for mathematics educators and teachers suggesting instructional strategies to teach the limit of a function, ensuring conceptual understanding; for students in developing deeper understanding of the concept of the limit of a function; and for textbook authors in developing tasks, activities, and materials that support meaningful engagement with the concept of limit.